M32 Effect of pirfenidone on all-cause mortality (acm) and forced vital capacity (fvc) in idiopathic pulmonary fibrosis (ipf) patients with low fvc and/or low dlco: analysis of pooled data from ascend and capacity. (15th November 2017) - Nathan, SD; Costabel, U; Albera, C; Kirchgaessler, KU; Chou, W; Noble, PW
Abstract : Introduction: The pivotal trials of the two approved therapies in IPF, pirfenidone and nintedanib, assessed patients with protocol-defined mild to moderate disease. The effect of pirfenidone in patients with more severe lung function impairment warrants further investigation. Pooled Results from ASCEND and CAPACITY studies (NCT01366209, NCT00287729 and NCT00287716 ) showed a significant reduction at 12 months in the risk of ACM (hazard ratio [HR], 0.52; 95% CI, 0.31, 0.87) 1 and in decline of percent predicted FVC (%FVC; 14.8% vs. 26.3% patients with ≥10% decline in%FVC or death, p<0.0001) 2 for patients treated with pirfenidone vs. placebo. We present pooled subgroup analyses from ASCEND and CAPACITY for patients with low baseline%FVC (<50%) and/or low percent predicted diffusing capacity for carbon monoxide (%DLCO <35%) to further inform on treatment effect of pirfenidone in patients with more severe lung function impairment. Methods: ACM was compared using the log-rank test, and HR was estimated using Cox regression. The categorical change in%FVC was summarised with the percent of patients with a≥10% absolute decline or death, and treatment comparison was performed using the rank ANCOVA method. Annual rate of FVC decline was estimated using the mixed-effects model. Results: 170 patients (90 pirfenidone, 80 placebo) had low%DLCO (n=157) or%FVC (n=13) at baseline. Treatment with pirfenidone was associated with a 72% reduction in risk of ACM over 12 months vs. placebo (4 vs. 12 deaths; HR, 0.28; 95% CI, 0.09, 0.86; p = 0.018; Table ). There was a 56% relative reduction in the proportion of patients with a ³10% absolute decline in%FVC or death at 12 months vs. placebo (18.9% vs. 42.5%; p = 0.0038). The annual rates of FVC decline were 150 and 278 mL in the pirfenidone and placebo arms, respectively (p = 0.003). Conclusions: Treatment with pirfenidone resulted in clinically meaningful benefits for ACM and FVC decline in patients with baseline%FVC <50% and/or%DLCO <35%. These data suggest that patients with more severe lung function impairment can also benefit from pirfenidone therapy. References: . King TE Jr, et al. N Engl J Med2014;370:2083–2092. . Noble PW, et al. Eur Resp J 2016;47:27–30.